Exes speak out, Narratives of apostasy: Jehovah's Witnesses, Scientology and Soka Gakkai. (13th February 2018) - Pannofino, Nicola; Cardano, Mario
Abstract : The paper presents a study of the trajectories of apostasy from three religious movements, Jehovah's Witnesses, the Soka Gakkai Buddhist institute and the Church of Scientology, through the analysis of a body of autobiographical narratives posted online by Italian apostates. Even more than being the account of a past religious experience, these narratives are the last stage in the gradual articulation of a voice with which the disaffected believers publicly express a critical view of the organizations they have left, charging them with using practices of interdiction to prevent dissent by their members. The common theme that emerges from these stories is not the loss of faith, but the discovery of a hidden deception, the breach of the implicit pact of trust that bound the narrator to the religious group.